Draft genome sequence of a multidrug-resistant Stenotrophomonas sp. B1-1 strain isolated from radiation-polluted soil and its pathogenic potential. (March 2021) - Wang, Yuxian; Dai, Zijie; Zhang, Zhidong; Zhu, Liying; Zhang, Hongman; Huang, He; Jiang, Ling
Abstract: Objectives: Stenotrophomonas is a genus of Gram-negative bacteria with several potential industrial uses as well as an increasingly relevant pathogen that may cause dangerous nosocomial infections. Here we present the draft genome sequence of a multidrug-resistant Stenotrophomonas sp. B1-1 isolated from radiation-polluted soil in Xinjiang Uyghur Autonomous Region, China. Methods: The genome of Stenotrophomonas sp. B1-1 was sequenced using a BGISEQ-500 platform. The generated sequencing reads were de novo assembled using SOAPdenovo and the resulting sequences were predicted and annotated to identify antimicrobial resistance genes and virulence factors using the ARDB and VFDB databases, respectively. Results: The Stenotrophomonas sp. B1-1 genome assembly resulted in a total genome size of 4, 723, 769 bp with a GC content of 67.47%. There were 4280 predicted genes with 68 tRNAs, 2 rRNAs and 163 sRNAs. A number of antimicrobial resistance genes were identified conferring resistance to various antibiotics as well as numerous virulence genes. Conclusion: The genome sequence of Stenotrophomonas sp. B1-1 will provide timely information for comparison of the Stenotrophomonas genus and to help further understand the pathogenesis and antimicrobial resistance of this genus.